Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1002/bip.21077
|View full text |Cite
|
Sign up to set email alerts
|

Influence of charge and size of terminal amino‐acid residues on local conformational states and shape of alanine‐based peptides

Abstract: We present results of conformational studies by Circular dichroism and NMR spectroscopy, differential scanning calorimetry, and molecular dynamics, of three alanine-based peptides: Ac-KK-(A)(7)-KK-NH(2) (KAK), Ac-OO-(A)(7)-DD-NH(2) (OAD), and Ac-KK-(A)(7)-EE-NH(2) (KAE), where A, K, O, D, and E, denote alanine, lysine, ornithine, aspartic acid, and glutamic acid residues, respectively. For OAD and KAE, canonical MD simulations with time-averaged NMR-derived restraints demonstrate the presence of an ensemble of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 42 publications
5
30
0
Order By: Relevance
“…The results of this study, along with those of our previous work 27,28,36 support the hypothesis that the presence of likecharged residues at the ends of a chain reversal can stabilize its structure. It should be noted that, even though this hypothesis might sound counterintuitive, it is supported by the fact that polylysine chains form α-helical structures at low pH; 51 in these structures, lysine side chains point outside to shield the backbone from solvent.…”
Section: Discussionsupporting
confidence: 90%
“…The results of this study, along with those of our previous work 27,28,36 support the hypothesis that the presence of likecharged residues at the ends of a chain reversal can stabilize its structure. It should be noted that, even though this hypothesis might sound counterintuitive, it is supported by the fact that polylysine chains form α-helical structures at low pH; 51 in these structures, lysine side chains point outside to shield the backbone from solvent.…”
Section: Discussionsupporting
confidence: 90%
“…All peptides under study were synthesized by using the procedure described in our earlier work [11]. The purities of the peptides were 99.98 and 99.99 % for D7 and D9 M, respectively, as assessed by analytical HPLC and MALDI-TOF analyses.…”
Section: Peptide Synthesismentioning
confidence: 99%
“…This is an independently forming region whose folding is not induced by a b-hairpin and is consequently an excellent object by which to study the factors that influence b-hairpin formation. Results from our preliminary conformational studies of two original fragments of the N-terminal part of the FBP28 protein (1E0L: 12-18 D7 and the 1E0L: [11][12][13][14][15][16][17][18][19]; the D9 M is a point mutation of the sequence) [9] fragments suggest that these peptides do not form stable three-dimensional structures in solution (water). However, it was found that D7 forms a large fraction of bent conformations.…”
Section: Introductionmentioning
confidence: 99%
“…914 The unfolded peptide backbone clearly has conformation preferences that are sequence and context dependent. 1520 Thus, defining the conformations of peptides in unfolded states has become a problem of current interest and importance. Advances in this effort will enable construction of more accurate models of intrinsically disordered proteins, enable elucidation of fundamental principles of protein folding, and potentially help design novel functional peptide modulators of biological processes.…”
Section: Introductionmentioning
confidence: 99%